Assessment of Human Arm Bioelectrical Impedance using Microcontroller Based System - PAWAR, CHARU (International Journal of Integrated Engineering, 2020)
Background and aims: In a wide field of research, the devices available based on long-established methods for measurement of bioelectrical impedance are large in size, expensive and low in accuracy. In this research, a system is developed for the measurement of the segmental bioelectrical impedance of the human body with high accuracy and small of a size.Methods: Developed method uses multi-frequency to measure segmental bioelectrical impedance that follows four electrodes segmental measurement technique and is equipped with an impedance analyzer with a touch screen. Multi-frequency signals flow to the human body to measure bioelectrical impedance and also compare data measured by developing a device to standard device.Results: Data have been collected through a developed device and is being analyzed. The outcomes show that the relative error of measured amplitude at multi-frequency is less than 1.50% while the absolute error of phase is up to 10. Comparison between two devices shows that the accuracy parameter of the developed device is more than 98% with the standard device. A compatible correlation (~ 0.9993) can be seen between both devices that they measure a nearly equal impedance of left and right arm at the same frequency.Conclusions: Use of the developed device for the measurement of segmental bioelectrical impedance using multi-frequency, adequately enhances all trait of measurement as state-of-the-art facilities, small size and liberated to use due to simplicity.